Attitudes and perceptions of UPV-CM students on student fees a research study - Abasolo, Marjolyn
We studied the Attitudes and Perceptions of UPV-CM students on student fees. This paper aims to know the socio-economic and demographic profile of the UPV-CM students, know the coping mechanisms of our respondents, pinpoint various problems on dealing with student fees ans benefits of Assistance Programs to the UPV-CM students. This would help significantly in understanding the social and economic status of the students in the University. The information, data and derived conclusions from this study aim to help University officials in policy making concerning student fees by recommending progams to make the student cope with the problem on student fees. There were 40 respondents, 10 from First, Second and Third Year and 10 from the Fourth Year (BSM, BSBA, and BSA) UPV-CM students has been determined sample. We used questionnaire and at the same time there were personal interviews. The design of the study was a one-shot survey where the groups study the attitudes and perceptions of UPV_CM student o student fees.